Jumanji Adventure: Innovation Learning Media Ipas Elementary School - Lestari, Maghfirotul Firmaning; Saihan, Saihan; Usriyah, Lailatul (Journal of Educational Sciences, 2025)
Learning in elementary school requires active interaction between teachers, students, and learning resources to create meaningful experiences. However, the learning of Natural and Social Sciences (IPAS) often remains theoretical, resulting in low motivation and comprehension. This study aims to develop Jumanji Adventure, an interactive educational game, to enhance motivation, interest, and understanding of fifth-grade students on sound material and its properties. The research applies a Research and Development (R&D) method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation. Data were collected through observation, interviews, documentation, and questionnaires involving media experts, material experts, linguists, teachers, and learners. Data analysis combined qualitative techniques (reduction, presentation, conclusion) and quantitative techniques using a Likert scale to assess validity. Findings show that Jumanji Adventure is highly valid, with expert ratings indicating strong quality in media design, content, and language. Classroom implementation demonstrates improved student motivation, engagement, and comprehension, as learners become more enthusiastic, active in discussions, and able to answer questions effectively. Despite the relatively short play duration, which requires repetition to fit time allocation, this media proves suitable as an innovative learning tool. Overall, it fosters interactive, enjoyable learning aligned with the Independent Curriculum.